A multicentre audit to assess the effectiveness of the British Orthodontic Society 'Hold that Smile' retainer videos. (March 2020) - Valiji Bharmal, Rozana; Parker, Kate; Caldwell, Susi; Chia, Matt; Gillgrass, Toby; Jones, George; Hodge, Trevor; Mattick, Rye; Murray, Alison; Seehra, Jadbinder; Stephens, Sara; Cunningham, Susan
Introduction: Retention is a crucial part of orthodontic treatment; however, patients often do not wear their retainers as advised. The British Orthodontic Society developed the 'Hold that Smile' campaign in 2017, to improve patient knowledge about retention. Information is provided in two formats: a cartoon and a conventional film. Objective: To assess whether patients find the 'Hold that Smile' videos useful and whether they improved patients' intended retainer wear. The gold standard was that 90% of patients should intend to wear their retainers in the long term after watching the videos. Design: National multicentre audit. Setting: Nine units in the UK. Methods: Patients aged ⩾ 10 years, in fixed appliances or retention, watched the retainer videos and then completed a questionnaire that was designed specifically for this audit. Each unit collected data for approximately 30 patients. Results: Data were collected for 278 patients in total. The average age was 17.9 years; 64.4% of patients were female and 35.6% were male. Most patients (86.3%) watched both videos and, of these, 44.1% preferred the film, 31.3% preferred the cartoon and 24.6% had no preference. The majority of patients (81.3%) felt that the film provided them with new information, compared with a lower percentage (48.5%) for the cartoon. More patients said they would recommend the film (76.3%) compared with the cartoon (63.3%). Before watching the videos, 77.0% of patients felt they knew about long-term retainer wear and 74.3% of those intended to wear their retainers in the long term. After watching the videos, 96.4% of all patients thought they would now wear their retainers long term. Conclusion: After watching the videos, there was a notable increase in the number of patients planning to wear their retainers long term and the gold standard was met. Therefore, these videos may be beneficial in improving understanding and compliance with retention.